Long-term outcomes of intensity-modulated radiation therapy (IMRT) and high dose rate brachytherapy as adjuvant therapy after radical hysterectomy for cervical cancer. Issue 8 (11th June 2020) - Contreras, Jessika; Srivastava, Amar; Chundury, Anupama; Schwarz, Julie K; Markovina, Stephanie; Thaker, Premal H; Massad, L Stewart; Mutch, David G; Powell, Matthew A; Grigsby, Perry W; Lin, Alexander J
Abstract : Objective: Compared with 3D-planned pelvic radiation, intensity-modulated radiation therapy (IMRT) has been shown to reduce acute toxicity in cervical cancer patients after radical hysterectomy. This study evaluated late toxicity and patterns of failure after post-operative pelvic IMRT interdigitated weekly with high dose rate brachytherapy. Methods: This retrospective study included 53 cervical cancer patients treated between January 2006 and August 2019 with radical hysterectomy, lymphadenectomy, and post-operative IMRT and high dose rate brachytherapy. The decision to include chemotherapy was made by the treating gynecologic oncologist based on patient-specific criteria including positive pelvic lymph nodes, positive surgical margins, or positive parametrial invasion. The actuarial rates of genitourinary and gastrointestinal toxicity, vaginal cuff/regional nodal/distant failure, and overall survival were calculated using the Kaplan–Meier method. Results: Median follow-up was 70 months (range 5.4–148) months and age at diagnosis was 47 (range 24–73) years. The 2018 International Federation of Gynecology and Obstetrics (FIGO) clinical stages were IB1 (n=19), IB2 (n=7), IIB (n=7), IIIC1 (n=19), and IIIC2 (n=1). Median radiation dose delivered in 160 cGy daily fractions was 5120 (range 4640–5120) cGy. Median brachytherapy dose prescribed to the vaginal surface delivered in six weekly fractions was 2400 (range 1200–4800) cGy. Concurrent chemotherapy was delivered in 35 (66%) patients. There were no acute grade > 3 genitourinary or gastrointestinal toxicities. Late grade > 3 occurred in two (3.8%) patients, including a small bowel obstruction and a ureteral stricture. The 5-year actuarial rate for gastrointestinal or genitourinary toxicity was 1.9%. There were no vaginal cuff recurrences. The 5-year actuarial rates for regional nodal failure, distant failure outside the radiation field, any failure, and overall survival were 11%, 11%, 14%, and 85%, respectively. Conclusions: Post-operative IMRT with high dose rate brachytherapy for patients with cervical cancer is associated with excellent outcomes and limited rates of radiation-related non-hematologic toxicity.